NEW LEGAL REGULATIONS APPLIED TO FINANCIAL STATEMENTS INCREASES THE RESPONSIBILITY PUBLIC ACCOUNTANT - Polar Falcón, Ernesto Augusto (2011)
In the text of Law No. 29720 - “An Act to promote securities emissions and strengthens the capital market”, Article 5 states that companies and entities other than those that are under the supervision of Conasev, States must submit financial Statements from the year 2011, prepared by audit firms authorized by a school of public accountants of Peru, where the annual income from the sale of goods or services or total assets equal or exceed three thousand tax units (UIT) . This Article specifies the importance of such legislation, which allows the increase of professional auditing services, and promotes greater interest in the preparation of financial statements, raising the responsibility of the practitioner. We analyze various legislation, corporate and tax, identified by the accounting information requested, and the results of investigations conducted at the Institute of Chartered Accountants of Lima and the Schools that have the responsibility for the formation of a public accountant.